1999
DOI: 10.1109/94.775621
|View full text |Cite
|
Sign up to set email alerts
|

AC and DC performance of polymeric housing materials for HV outdoor insulators

Abstract: An experimental study was conducted to investigate the performance of several polymer outdoor insulator formulations under ac and dc electrical stresses, The performance of the polymers was evaluated in terms of their charge accumulation and decay characteristics as a function of humidity, and their tracking and erosion resistance. The results obtained from this study indicate that significant differences exist in surface charging phenomena between ac and dc.A likely contribution of dc polarization processes l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(18 citation statements)
references
References 11 publications
1
16
0
1
Order By: Relevance
“…DBA with increased currents and longer periods have been reported by Moreno et al as the mechanism that causes greater erosion of SiR under DC than AC [9]. Similar findings on insulators have also been found by Gustavson et al but with voltage determined to be the governing parameter irrespective of the type of voltage [10].…”
Section: Introductionsupporting
confidence: 78%
“…DBA with increased currents and longer periods have been reported by Moreno et al as the mechanism that causes greater erosion of SiR under DC than AC [9]. Similar findings on insulators have also been found by Gustavson et al but with voltage determined to be the governing parameter irrespective of the type of voltage [10].…”
Section: Introductionsupporting
confidence: 78%
“…Literature on this subject is scarce. As reported in [34], even under humid conditions, the lifetime of positive charge implanted under positive dc corona may be longer as compared to the charge deposited by ac or negative dc corona, indicating the surface charging plays a determining role in the process of hydrophobicity loss and recovery. Besides, when charging epoxy insulator surfaces by dc corona, it was observed in [35] that at higher relative humidity the mechanism of surface charge decay was dominated by electric conduction along the surface of the insulators.…”
Section: Introductionmentioning
confidence: 68%
“…The results indicate, with corona exposure time the progressive increase in oxidation and hydroxyl group formation on the PDMS was observed. Moreno and Gorur [6,12,13,14] used single needle-plane electrode arrangement to study the corona degradation of the polymer samples. It has been shown that the severity of degradation increases with the relative humidity and the applied mechanical stress (bending stress).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly a single needle-plate arrangement with tangential electrical stress has been used in [16], to accurately study the environmental factors on discharge intensity and the erosion of the material. With the advent of HVDC transmission lines and usage of polymeric insulators for HVDC applications, effort has been made in the literature [10,13,17] to study the effect of DC corona. Performance analysis of polymeric samples subjected to DC corona of both the polarities has been reported recently in [10].…”
Section: Introductionmentioning
confidence: 99%